Structural characteristics of mitochondrial genome of Spirobo-lus walkeri (Spirobolida: Spirobolidae), and phylogenetic analysis of Diplopoda - Zhang, Wenwen; Zhao, Shengjun; Li, Lingna; Li, Yingzhu; Liu, Hongyi; Cui, Peng (Frontiers in Genetics, 2025)
The phylogeny of Diplopoda, a group of ancient arthropod and an important component of modern terrestrial ecosystems, remains unclear. Here, the complete mitogenome of Spirobolus walkeri was determined. The newly sequenced complete mitogenome was circular DNA molecules with sizes of 14,879 bp. The mitogenome was composed of 37 genes and one control region. Negative AT-skews and positive GC-skews were found in whole mitogenome. The gene COX1 used CGA as the start codon, while the other PCGs utilized ATN (A, T, G) as the start codons; however, the sequence of the stop codon was variable. The Ser2 exhibited the highest usage bias. All tRNAs have typical cloverleaf structures, except trnS-AGC and trnM. Phylogenetic analysis showed that S. walkeri and Spirobolus bungii shared a close relationship and that they were also closely related with Narceus annularus. This study helps resolve taxonomic ambiguities among morphologically similar species and provides data to support the establishment of evolutionary benchmarks for millipedes, including gene rearrangements and variations in tRNA structure.